The Intriguing Role of TLR Accessory Molecules in Cardiovascular Health and Disease - Bezhaeva, Taisiya; Karper, Jacco; Quax, Paul H. A.; de Vries, Margreet R. (Frontiers in Cardiovascular Medicine, 2022)
Activation of Toll like receptors (TLR) plays an important role in cardiovascular disease development, progression and outcomes. Complex TLR mediated signaling affects vascular and cardiac function including tissue remodeling and repair. Being central components of both innate and adaptive arms of the immune system, TLRs interact as pattern recognition receptors with a series of exogenous ligands and endogenous molecules or so-called danger associated molecular patterns (DAMPs) that are released upon tissue injury and cellular stress. Besides immune cells, a number of structural cells within the cardiovascular system, including endothelial cells, smooth muscle cells, fibroblasts and cardiac myocytes express TLRs and are able to release or sense DAMPs. Local activation of TLR-mediated signaling cascade induces cardiovascular tissue repair but in a presence of constant stimuli can overshoot and cause chronic inflammation and tissue damage. TLR accessory molecules are essential in guiding and dampening these responses towards an adequate reaction. Furthermore, accessory molecules assure specific and exclusive TLR-mediated signal transduction for distinct cells and pathways involved in the pathogenesis of cardiovascular diseases. Although much has been learned about TLRs activation in cardiovascular remodeling, the exact role of TLR accessory molecules is not entirely understood. Deeper understanding of the role of TLR accessory molecules in cardiovascular system may open therapeutic avenues aiming at manipulation of inflammatory response in cardiovascular disease. The present review outlines accessory molecules for membrane TLRs that are involved in cardiovascular disease progression. We first summarize the up-to-date knowledge on TLR signaling focusing on membrane TLRs and their ligands that play a key role in cardiovascular system. We then survey the current evidence of the contribution of TLRs accessory molecules in vascular and cardiac remodeling including myocardial infarction, heart failure, stroke, atherosclerosis, vein graft disease and arterio-venous fistula failure.